Proteomics of rice and Cochliobolus miyabeanus fungal interaction: Insight into proteins at intracellular and extracellular spaces. Issue 20 (21st August 2014) - Kim, Jin Yeong; Wu, Jingni; Kwon, Soon Jae; Oh, Haram; Lee, So Eui; Kim, Sang Gon; Wang, Yiming; Agrawal, Ganesh Kumar; Rakwal, Randeep; Kang, Kyu Young; Ahn, Il‐Pyung; Kim, Beom‐Gi; et al.
<x xml:space="preserve">Abstract</x> Necrotrophic fungal pathogen Cochliobolus miyabeanus causes brown spot disease in rice leaves upon infection, resulting in critical rice yield loss. To better understand the rice–C. miyabeanus interaction, we employed proteomic approaches to establish differential proteomes of total and secreted proteins from the inoculated leaves. The 2DE approach after PEG‐fractionation of total proteins coupled with MS (MALDI‐TOF/TOF and nESI‐LC‐MS/MS) analyses led to identification of 49 unique proteins out of 63 differential spots. SDS‐PAGE in combination with nESI‐LC‐MS/MS shotgun approach was applied to identify secreted proteins in the leaf apoplast upon infection and resulted in cataloging of 501 unique proteins, of which 470 and 31 proteins were secreted from rice and C. miyabeanus, respectively. Proteins mapped onto metabolic pathways implied their reprogramming upon infection. The enzymes involved in Calvin cycle and glycolysis decreased in their protein abundance, whereas enzymes in the TCA cycle, amino acids, and ethylene biosynthesis increased. Differential proteomes also generated distribution of identified proteins in the intracellular and extracellular spaces, providing a better insight into defense responses of proteins in rice against C. miyabeanus. Established proteome of the rice–C. miyabeanus interaction serves not only as a good resource for the scientific community but also highlights its significance from biological aspects.